2022
DOI: 10.1037/ser0000623
|View full text |Cite
|
Sign up to set email alerts
|

Treating women incarcerated in or at-risk of restrictive placements: A statement of the problem and considerations for practice.

Abstract: Although limited, extant research suggests that incarcerated women are more likely than men to be placed in restrictive housing (e.g., administrative or disciplinary segregation) for disruptive behaviors that are linked to psychiatric symptomology and interpersonal deficits. Yet, few scholarly works discuss specific interventions or recommendations for treating incarcerated women in or at-risk of segregation. In this paper, we address the extent to which criminogenic and mental health needs of incarcerated wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…While existing research shows that young, Black men are overrepresented in restrictive housing units (Bonner et al, 2017; Labrecque & Mears, 2019), this gap is narrowing (Correctional Leaders Association & Liman Program, 2022) and it is relevant to know how various subgroups respond to SUSO. Batastini et al (2022) showed promising descriptive outcomes of SUSO for cis-gender women in restrictive housing including similar reductions in emotional distress and criminal attitudes, as well as fewer misconducts at 3-month posttreatment. Nonetheless, more rigorous investigations are needed.…”
Section: Discussionmentioning
confidence: 92%
“…While existing research shows that young, Black men are overrepresented in restrictive housing units (Bonner et al, 2017; Labrecque & Mears, 2019), this gap is narrowing (Correctional Leaders Association & Liman Program, 2022) and it is relevant to know how various subgroups respond to SUSO. Batastini et al (2022) showed promising descriptive outcomes of SUSO for cis-gender women in restrictive housing including similar reductions in emotional distress and criminal attitudes, as well as fewer misconducts at 3-month posttreatment. Nonetheless, more rigorous investigations are needed.…”
Section: Discussionmentioning
confidence: 92%
“…SUSO, reported by one survey respondent, can also be delivered in a primarily self-directed manner, but corrective feedback is recommended after all learning activities (Batastini et al, 2019). SUSO can also be modified to accommodate individual therapy or a small group format (Batastini et al, 2021). Barriers to service delivery included factors related to the restricted environment, absence of appropriate and targeted programming, and correctional staffing issues (e.g., staff shortages) that restrict service delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, more than half of their sample was unemployed, not including those with a disability. Batastini et al (2022) presented a nine-module program for persons in segregation that was piloted on women incarcerated in a state facility, targeting both mental health symptoms and criminal risk factors. With a small sample of 18 participants, the authors describe that treating both mental health symptoms as well as criminogenic needs related to decreases in behavioral health symptoms including decreases in depression and criminal thinking.…”
mentioning
confidence: 99%